Pengaruh Maintenance Sistem Indonesia National Single Window (INSW) terhadap Kelancaran Proses Clearance Kapal pada Perusahaan Keagenan Kapal di Surabaya - M. Firoos Anima Hazni; Lia Retian Asfirah; Endra Winarni (JURNAL TRANSMA, 2026)
The Indonesia National Single Window (INSW) is an integrated electronic system that supports the ship clearance process through the digital management of documents across institutions. Although it offers efficiency in port services, the system is vulnerable to disruptions when maintenance is not managed optimally. This issue is critical, as the smooth flow of national logistics increasingly depends on the stability of digital systems like INSW. This study aims to analyze the impact of INSW system maintenance on the smoothness of the ship clearance process in Ship Agency companies in Surabaya. A quantitative approach was used, with data collected through questionnaires distributed to 44 respondents. The data were analyzed using simple linear regression and the coefficient of determination. The results indicate that INSW system maintenance has a significant effect on the smoothness of ship clearance processes, with a significance value of 0.003. The coefficient of determination (R²) of 19.3% shows that the maintenance variable explains part of the variation in clearance smoothness, while the rest is influenced by other factors outside the model. These findings highlight the importance of structured maintenance management and the enhancement of human resource competencies to handle technical issues during maintenance, which is crucial for ensuring efficient and sustainable port operations.